The Stegana (sensu stricto) species from China, with morphological and molecular evidence (Diptera: Drosophilidae). Issue 1 (2nd January 2016) - Zhang, Yuan; Li, Tong; Chen, Hongwei
Abstract : Four new species of the subgenus Stegana ( sensu stricto ) were found and described from China: S . ( S. ) antha sp. nov., S . ( S. ) latiorificia sp. nov., S . ( S. ) huangjiai sp. nov. and S . ( S. ) nigrifoliacea sp. nov. Three known Stegana (s. str.) species from China: S . ( S .) antlia Okada, 1991, S. ( S .) cheni Sidorenko, 1997 and S. ( S .) emeiensis Sidorenko, 1997 are redescribed as supplementary information. A key to the species, based on morphological characters, is provided. The phylogenetic relationships among 14 species of the subgenus Stegana are reconstructed with the combined sequences of the mitochondrial genes, ND2 (NADH dehydrogenase subunit 2) and COI (cytochrome c oxidase, subunit I). Moreover, the intra- and interspecific pairwise K-2P (Kimura's two-parameter) distances among these species are summarized, and the availability of mitochondrial markers in the species identification of the subgenus Stegana are further discussed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:368C55C3-B101-457C-BD61-BDD8F1B780E5